2008
DOI: 10.1002/bdra.20464
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for detection of prenatal alcohol exposure: A critical review of fatty acid ethyl esters in meconium

Abstract: The accurate identification of alcohol-exposed pregnancies represents a significant challenge in the development of FAEE detection cutoffs to maximize the sensitivity and specificity of the test. We present several options for the improvement of exposure assessment in future studies of FAEE as biomarkers for PAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 38 publications
3
56
0
2
Order By: Relevance
“…110 Meconium testing only captures PAE late in the second and third trimesters of pregnancy and therefore may fail to identify a large proportion of infants at risk for alcohol-related harm. 60 In addition, currently available biomarkers have insufficient sensitivity to detect low levels of PAE, which is the most prevalent pattern of consumption among pregnant women. 1 An objective test that measures alcohol itself in breath, urine, or blood could detect lowlevel use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…110 Meconium testing only captures PAE late in the second and third trimesters of pregnancy and therefore may fail to identify a large proportion of infants at risk for alcohol-related harm. 60 In addition, currently available biomarkers have insufficient sensitivity to detect low levels of PAE, which is the most prevalent pattern of consumption among pregnant women. 1 An objective test that measures alcohol itself in breath, urine, or blood could detect lowlevel use.…”
Section: Discussionmentioning
confidence: 99%
“…72,75 To reduce the risk of bias, data were excluded from 1 study that looked at the agreement between self-reported drinking in the first trimester and meconium testing 75 because meconium does not begin to accumulate until the second and third trimesters. 60 We also excluded data from another study that compared self-reported PAE during the second trimester with postnatal tests of maternal EtG, EtS, GGT, CDT, and PEth in dried infant blood spots because of the short detection window of these biomarkers. 72 Of the remaining studies, 2 had an unclear risk of bias, and 3 had a high risk of bias.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another drawback in focusing on this biomarker is that FAEEs have been detected in the meconium from infants who have not been exposed to alcohol (Chan et al 2003), leading to false positives. Thus, further research is needed on the usefulness of FAEEs as a biomarker for prenatal alcohol exposure, and other biomarkers for maternal consumption of alcohol should be pursued (Burd and Hofer 2008;Datta et al 2008). …”
Section: Indirect and Direct Biomarkersmentioning
confidence: 99%
“…A detecção precoce da exposição pré-natal ao álcool, combinada com o monitoramento contínuo do progresso físico e mental do neonato, pode facilitar a intervenção, potencializando o desenvolvimento da criança, e prevenir doenças secundárias 33 . Dessa forma, é importante que o biomarcador de exposição pré-natal ao etanol seja específico e sensível, útil para identificar os neonatos com risco de DEAF 34 .…”
Section: Detecção Da Exposição Pré-natal Ao Etanolunclassified